Ultrasonographical and Angiographical Study on the Testes of Large White Yorkshire Pig (Sus scrofa) - Sikarwar, Seema (Indian Journal of Veterinary Anatomy, 2019)
The present ultrasonographical and angiographical study was conducted on the testes of 10 Large White Yorkshire pigs. The testicular parenchyma appeared homogenous with a coarse medium echo-pattern. The mediastinum testis appeared as a centrally located hyperechoic line extending up to three quarters of the testicular length when imaged in the saggital (longitudinal) plane. The mediastinum testis appeared as circular echogenic area in the mid portion of homogenous testicular parenchyma on transverse sonographic examination.The funicular part of the testicular artery was highly coiled and formed many loops which were irregularly arranged along the whole length of the vascular cone. The marginal portion of the testicular artery was the direct continuation of the funicular portion of the testicular artery on a level with the caput extremity.